Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.cell.2014.03.055
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Mesenchymal Function for miR-143/145 in Intestinal Epithelial Regeneration

Abstract: Summary Downregulation of the miR-143/145 microRNA (miRNA) cluster has been repeatedly reported in colon cancer and other epithelial tumors. In addition, overexpression of these miRNAs inhibits tumorigenesis, leading to broad consensus that they function as cell-autonomous epithelial tumor suppressors. We generated mice with deletion of miR-143/145 to investigate the functions of these miRNAs in intestinal physiology and disease in vivo. While intestinal development proceeded normally in the absence of these m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
173
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 193 publications
(187 citation statements)
references
References 61 publications
14
173
0
Order By: Relevance
“…More-detailed insights are required into the genetic and epigenetic mechanisms of miR-145 transcriptional regulation in the smooth muscle field and cancer. Besides its role in cancer progression, miR-145 has been found as one of the most enriched miRNAs in vascular smooth muscle cells (vSMCs), where miR-145 is required for vSMC maturation and further regulation of their plasticity and contractility (Albinsson and Swärd, 2013;Boettger et al, 2009;Chivukula et al, 2014;Cordes et al, 2009;Elia et al, 2009;Xin et al, 2009). Many miR-145 target genes have been shown to be involved in these processes; yet, our newly found connection to zeb1a and foxo1a in iSMCs also suggests that these two novel players might be involved in the regulation of smooth muscle cell plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…More-detailed insights are required into the genetic and epigenetic mechanisms of miR-145 transcriptional regulation in the smooth muscle field and cancer. Besides its role in cancer progression, miR-145 has been found as one of the most enriched miRNAs in vascular smooth muscle cells (vSMCs), where miR-145 is required for vSMC maturation and further regulation of their plasticity and contractility (Albinsson and Swärd, 2013;Boettger et al, 2009;Chivukula et al, 2014;Cordes et al, 2009;Elia et al, 2009;Xin et al, 2009). Many miR-145 target genes have been shown to be involved in these processes; yet, our newly found connection to zeb1a and foxo1a in iSMCs also suggests that these two novel players might be involved in the regulation of smooth muscle cell plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…In other tissues, miR‐143 impairs glucose metabolism through the induction of insulin resistance (Jordan et al ., 2011), regulates the contractility and maintenance of smooth muscle myoblasts (Elia et al ., 2009) and controls vascular remodelling following injury (Xin et al ., 2009) and intestinal epithelial regeneration (Chivukula et al ., 2014). …”
Section: Discussionmentioning
confidence: 99%
“…However, by other methods including RNA gel blot and qRT-PCR, these levels are significantly more equivalent. [28][29][30] Two studies have demonstrated wide differences in microRNA RPM depending on the use of different library preparation kits (TruSeq small RNA [Illumina], NEXTflex [Bioo Scientific], and NEBNext [New England Biolabs]), with some microRNAs having counts as high as 100,000 RPM by one method and <1,000 RPM by a different method from matched samples. 31,32 Thus in comparing studies, it is important to keep these concerns in mind and for all projects within a given laboratory or core sequencing facility be consistent in regards to the preparation method used.…”
Section: Microrna-seq Alignmentmentioning
confidence: 99%